Antimicrobial Potential of Biosynthesized Silver Nanoparticles by Aaronsohnia factorovskyi Extract - Fatimah Al-Otibi; Reem A. Al-Ahaidib; Raedah I. Alharbi; Rana M. Al-Otaibi; Gadah Albasher (Molecules, 2020)
The green biosynthesis of nanoparticles by plant extracts is an attractive and promising technique for medicinal applications. In the current study, we chose one of the daisy plants, Aaronsohnia factorovskyi (which grows in the Najd region, Saudi Arabia), to investigate its anti-microbial efficacy, in combination with silver nanoparticles. The biosynthesized nanoparticles were evaluated for antibacterial activity against Staphylococcus aureus, Bacillussubtilis (Gram-positive), Pseudomonas aeruginosa, and Escherichia coli, (Gram-negative) using the disc diffusion method, while the antifungal activity was assessed against Fusarium oxysporum, Fusarium solani, Helminthosporiumrostratum, and Alternariaalternata. The potential phytoconstituents of the plant extracts were identified by Fourier-transform infrared spectroscopy (FT-IR) techniques, the Field emission scanning electron microscopy (FE-SEM), Chromatography/Mass Spectrometry (GC-MS) techniques, and Zeta potential analysis. The current study revealed the ability of the tested plant extract to convert silver ions to silver nanoparticles with an average diameter of 104–140 nm. Biogenic Aaronsohnia factorovskyi-silver nanoparticles (AF-AgNPs) showed significant antibacterial activity against Staphylococcus aureus with inhibition zone diameter to 19.00 ± 2.94 mm, and antifungal activity against Fusarium solani, which reduced the growth of fungal yarn to 1.5 mm. The innovation of the present study is that the green synthesis of NPs, which is simple, cost-effective, provides stable nano-materials, and can be an alternative for the large-scale synthesis of silver nanoparticles.